Pengaruh Suasana Cafe Dan Kualitas Layanan Terhadap Kepuasan Konsumen Di Recceh Coffe - Ummah , Muhammad Fikrul; Muhajirin; Darmawan, Imam (CV ODIS, 2024)
This research aims to determine the influence of cafe atmosphere and service quality on consumer satisfaction at Recceh Coffee, which is measured by partial tests (t tests) and simultaneous tests (f tests). The population in this study is all consumers who have purchased at recceh cafes. The sampling technique uses the method purposive sampling with a sample size of 100 people. The research results show that: 1). The cafe atmosphere does not have a partial and significant effect on consumer satisfaction at Recceh Coffee; Service quality has a partial and significant effect on consumer satisfaction at Recceh Cafe. 2). The cafe atmosphere and service quality simultaneously and significantly influence consumer satisfaction at Recceh Cafe